Kebenaran yang Memerdekakan Kajian Hermeneutik-Literer dan Teologi Kontekstual Asia atas Yohanes, 8:30-34 - Leftungun, Everestus; Pius Didimus Huklubuk (Journal New Light, 2026)
This paper re-examines Jesus' words, "The truth will set you free" (John 8:32), highlighting the relationship between truth and freedom, which is often reduced to spiritual or moral readings. The research gap addressed is the lack of studies that integrate John's lexical-textual analysis with the crisis of truth and identity experienced by Asian communities, particularly Indonesia. Using a hermeneutic-literary method, this study examines the narrative structure of the pericope, the lexical meaning of key Greek terms (aletheia, eleutheroo, doulos), and the historical context of John's community, then connects these with Asian contextual theology. The results demonstrate that truth in John's Gospel is both personal and relational, rooted in Christ's revelation that renews human identity. Freedom is understood not as moral autonomy, but as existential transformation through a relationship with the Word that liberates from the power of sin and structures of injustice. The unique contribution of this study lies in its integrative approach that brings together Johannine exegesis with the Asian social context, thus offering a relevant theological framework for the Church in responding to relativism, manipulation of truth, and the ethical challenges of contemporary society.